Mathematics

Recommended readings

Syntax Guides

​
a2+b2=c2a^2 + b^2 = c^2
Ξ±+Ξ²+Ξ΄+ΞΈ+ϕρ\alpha + \beta +\delta+\theta +\phi \rho
Consider (eq:a):
​
$ \alpha = \beta $ (a)
@equation(id)x=βˆ‘i=1Ni@/@equation(id) x = \sum_{i=1}{N} i @/
@equation(id)
x = \sum_{i=1}{N} i
@/
$ y=\sum_{i=1}^n g(x_i) $
(a+b)3=(a+b)2(a+b)=(a2+2ab+b2)(a+b)=(a3+2a2b+ab2)+(a2b+2ab2+b3)=a3+3a2b+3ab2+b3\begin{align} (a+b)^3 &= (a+b)^2(a+b)\\ &=(a^2+2ab+b^2)(a+b)\\ &=(a^3+2a^2b+ab^2) + (a^2b+2ab^2+b^3)\\ &=a^3+3a^2b+3ab^2+b^3 \end{align}
\begin{align}
(a+b)^3 &= (a+b)^2(a+b)\\
&=(a^2+2ab+b^2)(a+b)\\
&=(a^3+2a^2b+ab^2) + (a^2b+2ab^2+b^3)\\
&=a^3+3a^2b+3ab^2+b^3
\end{align}
​
\[
\left|\sum_{i=1}^n a_ib_i\right|
\le
\left(\sum_{i=1}^n a_i^2\right)^{1/2}
\left(\sum_{i=1}^n b_i^2\right)^{1/2}
\]